Exploring crossmodal correspondences for future research in human movement augmentation - Pinardi, Mattia; Di Stefano, Nicola; Di Pino, Giovanni; Spence, Charles (Frontiers in Psychology, 2023)
‘Crossmodal correspondences’ are the consistent matchings between perceptual dimensions or stimuli coming from different sensory domains, which have been widely observed in the general population and investigated in psychology, in recent years. At the same time, the emerging field of human movement augmentation (i.e., the enhancement of motor abilities by means of artificial devices) has been struggling with relaying supplementary information about the state of the artificial device and its interaction with the environment to the user, which may help the latter to control it efficiently. To date, this challenge has never been addressed by capitalizing on the emerging knowledge concerning crossmodal correspondence, despite it being tightly related to multisensory integration. In this perspective paper, we introduce crossmodal correspondences and human augmentation, then we consider three of the ways in which the former might impact the latter, and the feasibility of this process. First, crossmodal correspondences might facilitate the integration of device status information (e.g., position) coming from different sensory modalities (e.g., haptic and visual), thus increasing their usefulness for motor control and embodiment. Second, by capitalizing on their widespread and seemingly spontaneous nature, crossmodal correspondences might be exploited to reduce the cognitive burden caused by additional sensory inputs and the time required for the human brain to adapt the representation of the body to the presence of the artificial device. Third, to accomplish the first two points, crossmodal correspondences should be able to survive sensory substitution, a strategy commonly used when implementing supplementary feedback.